A molten salt regeneration method for retired lithium battery positive electrode material and application thereof in solid-state battery

CN122822930APending Publication Date: 2026-09-25ZHEJIANG UNIV OF TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610937029.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-26
Publication Date
2026-09-25

AI Technical Summary

Technical Problem

[0005]然而,现有熔盐修复技术存在以下不足:一是熔盐体系设计不完善,单一或简单二元锂盐熔点高、流动性差,难以实现均匀补锂与晶粒形貌调控;二是修复工艺与固态电池应用脱节,所得材料表面残碱高、界面阻抗大,无法满足固态电池对正极界面兼容性的要求;三是未能实现结构修复、形貌调控与表面包覆的同步协同,缺乏在单一熔盐体系中同步完成补锂修复与重金属表面改性的方法

Benefits of technology

第一,实现高效补锂与深度结构修复。通过草酸锂重结晶在正极表面实现均匀分散,低温补锂后于高温下形成熔融锂盐液相介质,提供优异的锂离子传输环境,克服了现有熔盐体系流动性差、补锂不均的问题,获得高结晶度、低阳离子混排的再生材料。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122822930A_ABST
    Figure CN122822930A_ABST
Patent Text Reader

Abstract

The application discloses a kind of retired lithium battery positive electrode material molten salt regeneration method and its application in solid-state battery. Belong to waste battery regeneration technical field. The method includes: retired ternary positive electrode material is dispersed in lithium oxalate solution, dropwise added to ethanol to carry out lithium oxalate recrystallization, then first low-temperature lithium supplement and preliminary structure repair are carried out, then mixed with metal oxide additive and carried out high-temperature calcination. Lithium oxalate forms molten state liquid phase medium at high temperature, and heavy metal oxides react with surface lithium in molten salt, and a stable coating layer with good lithium ion conduction capacity is constructed in situ. The coating layer effectively inhibits the excessive growth of grains during the regeneration process, forming a uniform nano-single crystal structure. Crystal structure reconstruction, grain morphology control and in-situ surface modification are completed simultaneously. The prepared regenerated positive electrode material has the advantages of low surface residual alkali, high crystallinity, low cation mixing and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of waste lithium-ion battery recycling technology, specifically relating to a method for recycling and reusing positive electrode materials from waste nickel-cobalt-manganese ternary lithium batteries. Background Technology

[0002] In recent years, the production and stock of lithium-ion batteries have continued to climb, maintaining a leading position among various rechargeable batteries. However, the widespread use of lithium-ion batteries has also led to a sharp increase in the number of retired batteries. According to industry forecasts, the world will face the pressure of disposing of millions of tons of retired lithium-ion batteries within the next five years. Against this backdrop, the efficient, environmentally friendly, and economical recycling of retired lithium-ion batteries has become a key factor restricting the sustainable development of the new energy industry.

[0003] Currently, recycling technologies for cathode materials from retired lithium-ion batteries are mainly divided into two categories: pyrometallurgy and hydrometallurgy. Pyrometallurgical processes convert metal components into alloys or oxides through high-temperature roasting. While the process is relatively short, it suffers from high energy consumption, low recovery rates of valuable metals, and difficulties in waste gas treatment. Hydrometallurgical processes use acid / alkali leaching and solvent extraction to separate and purify metal elements. Although they can achieve higher metal recovery rates, the process is lengthy, consumes large amounts of chemical reagents, and incurs high wastewater treatment costs, resulting in significant environmental pressure. Furthermore, both of these traditional methods are essentially destructive recycling methods, exhibiting inherent drawbacks such as complex processes, high energy consumption, severe secondary pollution, and poor economic viability.

[0004] To address the shortcomings of traditional methods, researchers have proposed direct repair and regeneration technologies. These technologies achieve direct reuse of materials without damaging the crystal structure of the cathode material, through methods such as lithium replenishment and repair of lattice defects. Among these, the molten salt method has attracted widespread attention due to its advantages such as uniform heat transfer, mild reaction conditions, and fast ion diffusion rates. For example, patent CN202310908097.5 discloses a molten salt repair and recycling method for waste ternary cathode materials. This method involves mixing waste cathode precursor powder with molten salt, a nickel source, a manganese source, and a cobalt source, performing multi-stage calcination in an oxygen atmosphere, and then washing and drying to obtain molten salt-repaired ternary cathode materials.

[0005] However, existing molten salt repair technologies have the following shortcomings: First, the molten salt system design is imperfect; single or simple binary lithium salts have high melting points and poor fluidity, making it difficult to achieve uniform lithium replenishment and grain morphology control. Second, the repair process is disconnected from solid-state battery applications, resulting in high residual alkali and high interfacial impedance on the surface of the material, failing to meet the compatibility requirements of solid-state batteries for the cathode interface. Third, the simultaneous synergy of structural repair, morphology control, and surface coating is not achieved; there is a lack of methods to simultaneously complete lithium replenishment repair and heavy metal surface modification in a single molten salt system. For example, existing patent CN 121149475 A discloses a lithium-ion battery cathode material regeneration method based on the synergistic effect of doping and molten salt reconstruction, which specifically uses a eutectic salt combination of LiOH-NaCl or LiOH-Na2SO4 as the molten salt system, simultaneously introducing Nb during high-temperature lithium replenishment and structural reconstruction. 5+ / Ta 5+ / Mo 6+ Bulk doping is performed to anchor lattice oxygen by forming high-bond-energy TM–O bonds in the crystal lattice, thereby suppressing oxygen vacancy generation and high-voltage oxygen evolution reaction, thus improving the structural stability and rate performance of the regenerated material under high voltage. However, the method proposed in this patent still has key flaws: First, its molten salt system is essentially a mixture of molten alkali and sodium salt, which has limited fluidity and insufficient lithium-ion transport efficiency at high temperatures, making it difficult to achieve uniform and controllable morphology of the cathode material grains. Second, this patent achieves bulk doping by introducing high-valence metal ions into the crystal lattice, rather than constructing a lithium-ion conductive coating layer on the particle surface. This has extremely limited effect on reducing the residual alkali content on the cathode material surface and suppressing side reactions between the cathode and the inorganic solid electrolyte, and cannot effectively reduce the cathode / solid electrolyte interface impedance. Third, the method in this patent only achieves the synergy of the two functions of "doping + molten salt reconstruction", failing to organically unify the three functions of structural repair, grain morphology control and surface interface modification. In particular, it cannot simultaneously complete the in-situ construction of the surface coating layer in a single molten salt system, thus failing to fully meet the special requirements of solid-state batteries for cathode material interface compatibility.

[0006] In summary, existing technologies for recycling cathode materials from retired lithium-ion batteries suffer from problems such as complex processes, high energy consumption, and poor environmental friendliness. Meanwhile, existing molten salt remediation methods have shortcomings in terms of molten salt system composition, remediation process control, and product functionalization design. Therefore, there is an urgent need to develop a simple, low-energy-consumption, environmentally friendly method that can achieve high-value regeneration of cathode materials, particularly one that can simultaneously complete structural repair, morphology control, and surface functionalization modification to meet the high-performance requirements of solid-state batteries for cathode materials. Summary of the Invention

[0007] To address the aforementioned problems, this invention proposes a novel molten salt regeneration method for retired lithium-ion battery cathode materials. The key lies in: achieving uniform dispersion of lithium oxalate on the cathode surface through recrystallization; utilizing the molten liquid phase medium formed by the high-temperature decomposition of lithium oxalate to promote lithiation; and simultaneously allowing heavy metal oxide additives (at least one of niobium pentoxide, molybdenum trioxide, tantalum pentoxide, and tungsten pentoxide) to react with lithium on the cathode material surface in the molten salt environment, thereby constructing a stable coating layer with lithium-ion conductivity in situ. This coating layer not only effectively reduces surface residual alkali and improves interfacial compatibility with the solid electrolyte, but also inhibits excessive grain growth during regeneration, forming a uniform nanocrystalline structure. Thus, crystal structure reconstruction, grain morphology control, and in-situ surface modification are simultaneously completed in a single molten salt system, overcoming the high cathode / solid electrolyte interfacial impedance defects that are difficult to address in existing bulk doping methods.

[0008] The specific technical solution adopted in this invention is as follows: A method for molten salt regeneration of retired lithium battery cathode materials specifically includes the following steps: S1: Disperse retired ternary cathode material in lithium oxalate solution, add the resulting mixture dropwise to ethanol solution for recrystallization, filter and dry, and then sinter the resulting solid at low temperature in an oxygen-containing atmosphere to replenish lithium and perform preliminary structural repair to obtain pre-regenerated material; S2: The pre-regenerated material is mixed evenly with metal oxide additives, and then calcined at high temperature in an oxygen-containing atmosphere. Crystal structure reconstruction, grain morphology control and in-situ surface modification are completed simultaneously in the molten salt liquid phase medium to obtain a regenerated cathode material coated with a coating layer.

[0009] This invention disperses retired ternary cathode material in a lithium oxalate solution, then adds it dropwise to ethanol for lithium oxalate recrystallization. This reduces the lithium oxalate particle size and achieves uniform dispersion on the cathode surface. Reducing the particle size allows for more uniform mixing of the lithium source and cathode, and also promotes decomposition, thus facilitating full lithiation of the waste cathode during regeneration. After filtration and drying, low-temperature lithium replenishment and preliminary structural repair are performed, followed by mixing with metal oxide additives (at least one of niobium pentoxide, molybdenum trioxide, tantalum pentoxide, and tungsten pentoxide), and then high-temperature calcination. At high temperatures, lithium oxalate forms a molten liquid phase medium that can penetrate to the grain boundaries of the raw materials, enabling primary particle separation and facilitating the formation of uniformly dispersed nanocrystals. Simultaneously, crystal structure reconstruction, grain morphology control, and in-situ surface modification are achieved. The key innovations of this invention are as follows: Firstly, through the recrystallization process of lithium oxalate, fine and uniform lithium oxalate particles are obtained, promoting the formation of a uniform high-temperature liquid-phase reaction environment. Secondly, heavy metal oxides react with lithium on the surface of the cathode material in molten salt, constructing a stable coating layer with good lithium-ion conductivity in situ. This coating layer also effectively inhibits excessive grain growth during the regeneration process, forming a uniform nanocrystalline structure. The resulting regenerated cathode material has advantages such as low surface residual alkali, high crystallinity, and low cation mixing. It exhibits excellent interfacial compatibility and significantly reduced interfacial impedance with inorganic solid electrolytes, and can be directly used as the cathode material for high-performance solid-state lithium-ion batteries.

[0010] Further, in step S1, the retired ternary cathode material is cathode powder recovered from lithium-ion batteries that have reached the end of their cycle life (capacity retention ≤ 80%), and its chemical composition is LiNi. x Co y Mn z O2 or LiNi x Co y Mn z O2, where x+y+z=1, and 0.3≤x≤0.9, 0.05≤y≤0.3, 0.05≤z≤0.4; in the retired ternary cathode material, the lithium loss is 5%~30%, the surface residual alkali content is 0.5~10.0 wt%, and the cation mixing degree is 3%~10%.

[0011] Further, in step S1, the mass ratio of the decommissioned ternary cathode material to the lithium oxalate solution is 1:10 to 1:50; the concentration of the lithium oxalate solution is 0.2-1.0 mol / L, and the lithium oxalate solution is an aqueous solution of lithium oxalate.

[0012] Furthermore, in step S1, the rate of dropwise addition is 1 to 5 mL / min; more preferably, the dropwise acceleration rate is 2 to 3 mL / min.

[0013] Furthermore, in step S1, after dropwise addition, stirring is continued for 0.1 to 2 hours to allow for sufficient recrystallization; more preferably, the stirring time is 0.5 to 1 hour; and more preferably, the stirring rate is 500 to 800 rpm. Stirring at this speed can further suppress the continued growth after nucleation, so as to obtain lithium oxalate crystals with smaller particle sizes, and avoid the large particle size affecting the uniformity of lithium oxalate dispersion in the waste NCM cathode and the subsequent lithium replenishment effect.

[0014] Further, in step S1, the volume ratio of the mixture to the ethanol solution is 1:2 to 1:10; more preferably, the volume ratio is 1:3 to 1:5; even more preferably, the ethanol solution is anhydrous ethanol or an aqueous solution of ethanol with a volume fraction ≥95%.

[0015] Furthermore, in step S1, the time for low-temperature sintering lithium replenishment and preliminary structural repair is 2-6 hours, the sintering temperature is 300-500℃, and the sintering atmosphere is an oxygen-containing atmosphere.

[0016] Furthermore, in step S2, the amount of metal oxide additive added is 0.5%-5% of the mass of the pre-regenerated material, and even more specifically, 0.5%-2%.

[0017] Furthermore, in step S2, the high-temperature calcination time is 6-12 hours, the sintering temperature is 800-1000℃, and the sintering atmosphere is an oxygen-containing atmosphere.

[0018] Further, in step S2, the metal oxide additive is at least one of niobium pentoxide, molybdenum trioxide, tantalum pentoxide, and tungsten pentoxide.

[0019] Furthermore, in step S2, during the high-temperature calcination process, the metal oxide additive reacts with lithium on the surface of the cathode material to construct a stable coating layer with lithium-ion conductivity in situ. Simultaneously, this coating layer inhibits excessive grain growth during regeneration, forming a uniform nanocrystalline structure. Furthermore, in steps S1 and S2, the heating rate is 2-10°C / minute.

[0020] Furthermore, in steps S1 and S2, the oxygen-containing atmosphere is an oxygen-containing atmosphere with an oxygen volume ratio of 20% to 100%, more preferably at least one of air and oxygen.

[0021] This invention also provides a regenerated cathode material prepared by the above method. The regenerated cathode material has a layered structure with a nanocrystalline single-crystal morphology, a particle size of 200-800 nm, more preferably 400-800 nm, and is coated with a lithium-conducting layer containing at least one of niobium, molybdenum, tantalum, and tungsten. More preferably, the lithium-ion conducting layer is at least one of LiNbO3, Li2MoO4, LiTaO3, or Li2WO4, and the coating thickness is 5-30 nm. The residual alkali (Li2CO3 / LiOH) content on the surface of the regenerated cathode material is ≤0.2 wt.%.

[0022] The present invention also provides a solid-state battery cathode comprising the above-mentioned recycled cathode material.

[0023] The present invention also provides a solid-state battery comprising the above-described positive electrode.

[0024] Furthermore, this invention also provides the application of the above method in the fields of resource recycling of retired lithium batteries and solid-state batteries and cathode materials and their preparation.

[0025] Compared with existing technologies, the molten salt regeneration method for retired lithium battery cathode materials provided by this invention has the following advantages: First, it achieves efficient lithium replenishment and deep structural repair. Lithium oxalate is recrystallized to achieve uniform dispersion on the cathode surface. After low-temperature lithium replenishment, a molten lithium salt liquid phase medium is formed at high temperature, providing an excellent lithium-ion transport environment. This overcomes the problems of poor fluidity and uneven lithium replenishment in existing molten salt systems, resulting in regenerated materials with high crystallinity and low cation mixing.

[0026] Second, an in-situ lithium-ion conductive coating layer is constructed to reduce surface residual alkali and interfacial impedance. Heavy metal oxides react with residual lithium on the cathode surface in molten salt to generate conductive layers such as LiNbO3 and Li2MoO4 in situ, transforming the traditional "bulk doping" into "surface interface engineering". This significantly reduces the surface residual alkali content, suppresses side reactions with the solid electrolyte, and greatly reduces interfacial impedance.

[0027] Third, the coating layer confines grain growth, simultaneously forming a uniform nanocrystalline structure. At high temperatures, the surface coating layer effectively suppresses excessive grain boundary migration and restricts abnormal grain growth, resulting in a 400-800 nm nanocrystalline structure. This structure shortens the lithium-ion diffusion path and improves solid-solid contact, achieving a synergistic effect of "lithium replenishment repair - surface coating - morphology control" in a single molten salt system. This provides a novel technical pathway for the direct regeneration of retired cathode materials into high-performance solid-state battery cathode materials.

[0028] Fourth, the process is simple, environmentally friendly, and economically efficient. This invention eliminates the need for complex acid / alkali leaching and solvent extraction steps, resulting in a short process flow and easy operation. The molten salt used can be recovered and recycled through washing, generating no large amounts of waste liquid or gas, thus meeting the requirements of a green circular economy. Simultaneously, this method achieves high-value direct regeneration of retired cathode materials, avoiding the loss of valuable metal elements in traditional methods, and possesses significant economic benefits and industrialization prospects.

[0029] In summary, this invention provides a molten salt regeneration method that integrates lithium replenishment repair, size and morphology control, and surface modification, providing an effective technical path for the green and high-value utilization of retired lithium-ion battery cathode materials and their reuse in solid-state batteries. Attached Figure Description

[0030] Figure 1 This is a SEM image of the regenerated positive electrode active material obtained in Example 1 of the present invention; Figure 2 This is a TEM image of the regenerated positive electrode active material obtained in Example 1 of the present invention; Figure 3 The image shows the XRD pattern of the regenerated positive electrode active material obtained in Example 1 of this invention. Figure 4 This is a SEM image of the positive electrode active material obtained in Comparative Example 1 of the present invention. Detailed Implementation

[0031] To better clarify and understand the objectives, process solutions, and advantages of this invention, the technical solutions and implementation methods of this invention will be further described clearly, completely, and in detail below through specific embodiments and in conjunction with the accompanying drawings. It should be understood that the embodiments described in this invention are implemented under the premise of the technical solutions of this invention, providing detailed implementation methods and specific operating procedures, but are only some embodiments of this invention, not all embodiments. The specific implementation methods described are limited to illustrating and explaining this invention and do not limit this invention. Based on the embodiments of this invention, all other implementation methods obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0032] Unless otherwise specified, the experimental methods and conditions used in the embodiments of this invention are conventional methods and conditions. The materials, reagents, instruments, and equipment used in the embodiments, unless otherwise specified, are all conventional substances or equipment known to those skilled in the art and can be obtained commercially or prepared by conventional methods. The reaction conditions described in the invention can all achieve the reactions and obtain the desired products. Due to space limitations, some embodiments are listed below to further illustrate the advantages of the technical solution of this invention. Unless otherwise specified, all proportions in the embodiments of this invention are mass ratios.

[0033] Example 1 Retired NCM622 cathode material: obtained from spent lithium-ion batteries with terminated cycle life and capacity retention ≤80% after dismantling, crushing, screening, and heat treatment (conventional treatment to burn off carbon and binders, etc.). Its chemical composition, determined by ICP-OES, is Li. 0.88 Ni 0.6 Co 0.2 Mn 0.2 O2, lithium loss of approximately 12%, surface residual alkali content of 1.8 wt%, and cation mixing degree of approximately 5%.

[0034] The above-mentioned decommissioned cathode material was added to a 0.5 mol / L lithium oxalate aqueous solution at a mass ratio of 1:30 and ultrasonically dispersed for 30 min to form a uniform suspension. This suspension was then added dropwise to anhydrous ethanol under vigorous stirring at a preferred stirring rate of 500-800 rpm and a preferred dropping rate of 2-3 mL / min. The volume ratio of the suspension to anhydrous ethanol was 1:3-5. Lithium oxalate has extremely low solubility in ethanol and rapidly recrystallizes onto the surface of the cathode material. After stirring (preferably at 500-800 rpm) for 30 min, the mixture was filtered. The resulting solid was vacuum dried at 80℃ for 12 h to obtain a waste cathode material with a uniform surface coating of lithium oxalate nanocrystals, with lithium oxalate particle sizes of approximately 200-400 nm.

[0035] The above-mentioned mixture was placed in a tube furnace and heated to 400°C at a rate of 5°C / min under air atmosphere, and held at that temperature for 4 hours. This allowed the lithium ions released from the decomposition of lithium oxalate to intercalate into the lithium vacancies in the decommissioned cathode material, completing the low-temperature lithium replenishment and preliminary repair of the layered structure. After natural cooling to room temperature, the pre-regenerated material was obtained.

[0036] The aforementioned pre-regenerated material was mixed uniformly with the heavy metal oxide additive niobium pentoxide (Nb₂O₅) at a mass ratio of 100:1.5. The mixed powder was placed in an alumina crucible and heated to 900°C at a rate of 5°C / min under air atmosphere, and held at that temperature for 10 h. During this process, the molten lithium salt (Li₂CO₃ / Li₂O) formed by the complete decomposition of lithium oxalate constitutes the liquid phase medium. Nb₂O₅ reacts with the residual lithium on the surface of the cathode material to generate a LiNbO₃ coating layer with a thickness of approximately 10 nm in situ. At the same time, this coating layer effectively inhibits excessive grain growth and promotes the formation of a uniform nanocrystalline structure.

[0037] The composite cathode is made by uniformly mixing regenerated cathode material and inorganic solid electrolyte Li6PS5Cl in a mass ratio of 7:3, with the active material loading controlled at 5-10 mg / cm³. 2In an argon glove box (water and oxygen < 0.1 ppm), Li6PS5Cl powder was first cold-pressed into an electrolyte sheet with a thickness of 300 μm. Then, composite cathode powder was spread on one side, and a surface-modified lithium metal anode (N / P ratio approximately 2.0) was placed on the other side. The layers were then cold-pressed layer by layer at 200 MPa to ensure tight adhesion between the interfaces, ultimately assembling a 2032-type all-solid-state button battery for electrochemical testing. The initial discharge specific capacity at 0.1 C was 168 mAh / g, and the capacity retention rate after 50 cycles was 92%.

[0038] The original electrochemical performance of the retired NCM622 cathode material used in this example, in its unretired state, is as follows: initial discharge specific capacity of 155 mAh / g at 0.1C, and capacity retention of 88% after 50 cycles. This demonstrates that the present invention not only achieves material regeneration but also results in superior performance. This is because the smaller single crystals can have more sufficient contact with the solid electrolyte, which is beneficial for capacity utilization and stable battery cycling. In contrast, the original material consists of secondary spherical particles of approximately 10 micrometers, which do not have adequate contact with the solid electrolyte in certain areas, thus hindering electrochemical performance.

[0039] Example 2 The rest is the same as in Example 1, except that the mass ratio of the decommissioned ternary cathode material to the lithium oxalate solution is changed to 1:10, and the concentration of the lithium oxalate solution is 1 mol / L.

[0040] Example 3 The remaining operations are the same as in Example 1, except that the mass ratio of the decommissioned ternary cathode material to the lithium oxalate solution is changed to 1:50, and the concentration of the lithium oxalate solution is 0.2 mol / L.

[0041] Example 4 The remaining operations are the same as in Example 1, except that the sintering temperature during the low-temperature lithium replenishment stage is 300°C, the sintering time is 6 hours, and the heating rate is 2°C / minute.

[0042] Example 5 The remaining operations are the same as in Example 1, except that the sintering temperature during the low-temperature lithium replenishment stage is 500°C, the sintering time is 2 hours, and the heating rate is 10°C / minute.

[0043] Example 6 The remaining operations are the same as in Example 1, except that the heavy metal mixture used is tantalum pentoxide (Ta2O5), and the amount added is 0.8 wt%.

[0044] Example 7 The remaining operations are the same as in Example 1, except that the heavy metal mixture used is Nb2O5 (1.2 wt%) + MoO3 (0.8 wt%).

[0045] Example 8 The remaining operations are the same as in Example 1, except that the heavy metal mixture used is tungsten pentoxide (W2O5), and the amount added is 0.5wt%.

[0046] Example 9 The remaining operations are the same as in Example 1, except that the heavy metal mixture used is molybdenum trioxide (MoO3), and the amount added is 2wt%.

[0047] Example 10 The remaining operations are the same as in Example 1, except that the high-temperature calcination temperature is 800℃, the sintering time is 12 hours, and the heating rate is 2℃ / minute.

[0048] Example 11 The remaining operations are the same as in Example 1, except that the high-temperature calcination temperature is 1000℃, the sintering time is 6 hours, and the heating rate is 10℃ / minute.

[0049] Example 12 The remaining operations are the same as in Example 1, except that the high-temperature calcination atmosphere is pure oxygen.

[0050] Example 13 The remaining operations are the same as in Example 1, except that the atmosphere has an oxygen volume ratio of 50%.

[0051] Example 14 The remaining operations are the same as in Example 1, except that the stoichiometric ratio of the waste ternary cathode material used is Li. 0.95 Ni 0.9 Co 0.05 Mn 0.05 O2, lithium loss of 5%, surface residual alkali content of 0.5wt%, the mass ratio of retired ternary cathode material to lithium oxalate solution was changed to 1:10, and the sintering atmosphere was pure oxygen.

[0052] Example 15 The remaining operations are the same as in Example 1, except that the stoichiometric ratio of the waste ternary cathode material used is Li. 0.7 Ni 0.34 Co 0.33 Mn 0.33 O2, lithium loss is 30%, and surface residual alkali content is 10wt%.

[0053] Comparative Example 1: The raw materials are the same as in Example 1, and no recycling measures are taken.

[0054] Comparative Example 2: The rest is the same as in Example 1, except that no heavy metal oxide additives are added.

[0055] Comparative Example 3: The remaining operations are the same as in Example 1, except that instead of low-temperature sintering, a single-stage sintering is used, in which the temperature is raised to 900°C at a rate of 5°C / min under an oxygen atmosphere and held for 12 hours for high-temperature calcination.

[0056] Comparative Example 4: The treatment object was the same as in Example 1, with the same mass of lithium oxalate Li2C2O4 powder as in Example 1, and 1.5wt% Nb2O5 of the total mass of the former added. The mixture was ground until homogeneous, resulting in lithium oxalate particles with a diameter of approximately 100-200 μm. The mixture was placed in an alumina crucible and subjected to low-temperature heat treatment at a heating rate of 5°C / min for 4 hours under an oxygen atmosphere. Then, the temperature was further increased to 900°C and held for 6 hours for high-temperature calcination.

[0057] Comparative Example 5: The rest is the same as in Example 1, except that the heavy metal additive used is niobium chloride (NbCl5).

[0058] Table 1. Preparation parameters for each example and comparative example.

[0059] Table 2 Structural parameters and electrochemical performance of each embodiment and comparative example

[0060] The conditions are summarized in Table 1, and the product properties and performance are shown in Table 2.

[0061] Based on the preparation parameters, structure, and electrochemical performance data of Examples 1-15 and Comparative Examples 1-5, the influence of various process factors on the regeneration effect of retired ternary cathode materials can be systematically analyzed. Firstly, in the lithium oxalate replenishment stage, the mass ratio and concentration of retired NCM622 cathode material to lithium oxalate solution significantly affect the regeneration performance. In Example 1, a 1:30 mass ratio of 0.5 mol / L lithium oxalate solution was used, resulting in the optimal particle size (~500 nm), and the recovered cathode material exhibited a complete structure (e.g., ...). Figure 1 The in-situ generated LiNbO3 coating layer is approximately 10 nm thick (e.g. Figure 2 The residual alkali content is only 0.06 wt%, the first-cycle discharge specific capacity reaches 168 mAh / g, and the cycle stability at 0.5C for 100 cycles reaches 96.2%. All its diffraction peaks belong to NCM diffraction peaks (e.g., Figure 3When the mass ratio was increased to 1:10 and the concentration to 1 mol / L (Example 2), the excessive lithium supplementation resulted in a slight increase in particle size and residual alkali, leading to a slight decrease in electrochemical performance. However, when the mass ratio was reduced to 1:50 and the concentration to 0.2 mol / L (Example 3), insufficient lithium supplementation resulted in a particle size increase to 760 nm, and both capacity and cycle retention were significantly lower than in Example 1, although good performance was still maintained. This indicates that the amount and concentration of lithium oxalate must be precisely matched to the degree of lithium loss in the decommissioned material; excessive or insufficient amounts are detrimental to the repair of the layered structure.

[0062] Secondly, the sintering parameters (temperature, time, and heating rate) in the low-temperature pre-regeneration stage are also crucial. In Example 1, under the conditions of holding at 400℃ for 4 h and heating rate of 5℃ / min, the lithium ions released from the decomposition of lithium oxalate could be fully inserted into lithium vacancies, while forming a uniform nano-lithium oxalate coating layer. If the temperature was lowered to 300℃ and the holding time was extended to 6 h (Example 4), although the residual alkali was slightly higher, the electrochemical performance was still close to that of Example 1, indicating that the lithium replenishment reaction was slower at lower temperatures but could still be completed. However, when the temperature was raised to 500℃ and the heating rate was increased to 10℃ / min (Example 5), the lithium oxalate decomposed too quickly, and the lithium ions could not be fully inserted before volatilization or the formation of unstable interfaces, resulting in an increase in residual alkali to 0.12 wt%. The capacity and cycle retention rate showed a significant downward trend, but were still better than the comparative examples. Therefore, it is necessary to control the appropriate temperature and heating rate in the low-temperature stage to ensure that the lithium source is uniformly and controllably embedded in the layered structure.

[0063] The type, dosage, and form of heavy metal additives have a significant impact on interface control and grain growth during the high-temperature calcination stage. Example 1 uses 1.5 wt% Nb₂O₅ to generate an in-situ LiNbO₃ coating layer, effectively inhibiting excessive grain growth (D). 50 =500 nm), and significantly reduced residual alkali to 0.06 wt%. Other additives such as Ta2O5 (Example 6) also showed good results, with the capacity slightly reduced to 167 mAh / g and the retention rate of 92.3%; while the mixed additives Nb2O5+MoO3 (Example 7), W2O5 (Example 8), or MoO3 alone (Example 9) could achieve a certain degree of performance recovery, but their cycle stability was slightly weaker than that of Nb2O5 alone. It is particularly noteworthy that Comparative Example 1 was done without any measures, and the resulting cathode material had broken particles (e.g., due to the unrepaired structure). Figure 4The performance level was low, with a first-cycle reversible capacity of only 126 mAh / g. In Comparative Example 2, without any heavy metal additives, the particle size of the recycled material increased to 1 μm. Although the residual alkali was low, the capacity was only 145 mAh / g, and the retention rate dropped to 70.3%, indicating that the lack of a coating layer leads to interfacial instability and exacerbated side reactions. Comparative Example 5 used niobium chloride (NbCl5) as an additive, introducing chloride ion impurities and failing to form a LiNbO3 layer, resulting in a residual alkali of up to 2.8 wt% and a capacity of only 140 mAh / g, further proving that additives in the form of heavy metal oxides are key to forming a surface lithium-conducting layer. However, the physical mixing in Comparative Example 4 also shows that even with the addition of heavy metal oxides, recrystallization is the key step in forming a coating layer. Although physical mixing alone can restore capacity to some extent, its cycle performance even decreases further.

[0064] High-temperature calcination parameters (temperature, time, heating rate) and atmospheric conditions also affect the crystal structure and electrochemical performance of the recycled material. The process parameters of 900℃, 10 h, and 5℃ / min in Example 1 achieved the optimal balance between particle size and electrochemical performance. If the calcination temperature was reduced to 800℃ and extended to 12 h (Example 10), although the capacity could still reach 165 mAh / g, the residual alkali increased to 0.15 wt%, and the cycle retention rate decreased to 89.2%, indicating that insufficient temperature led to incomplete coating reaction and inadequate removal of residual lithium salts. Conversely, when the temperature was increased to 1000℃ and shortened to 6 h (Example 11), the residual alkali further decreased to 0.04 wt%, but the particle size increased to 700 nm, and the capacity slightly decreased to 162 mAh / g, indicating that excessively high temperatures can cause excessive grain growth, impairing rate performance. Regarding the sintering atmosphere, Example 1 performed best in an air atmosphere. Example 12, using pure oxygen, had slightly lower capacity and retention rate than Example 1. Example 13, with a 50% oxygen atmosphere, fell between the two. This indicates that a moderate oxygen partial pressure is beneficial to the stability of the layered structure, but pure oxygen may over-oxidize the surface, which may slightly reduce the capacity.

[0065] Furthermore, this invention exhibits good applicability to decommissioned cathode materials with different compositions and lithium loss levels. Example 14 focuses on a high-nickel, low-lithium-loss material (Li). 0.95 Ni 0.9 Co 0.05 Mn 0.05 O2), the regenerated capacity reached 208 mAh / g, with a retention rate of 94.2%; while Example 15 targeted the high lithium loss NCM111 material (Li 0.7 Ni 0.34 Co 0.33 Mn 0.33(O2), the capacity was restored to 155mAh / g, with a retention rate of 93.7%. This shows that regardless of the nickel content or the degree of lithium deficiency in the material, the two-step method of this invention, combined with lithium oxalate recrystallization and heavy metal additives, can effectively achieve lithium replenishment, alkali reduction, and structural repair.

[0066] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the present invention in any way. Other variations and modifications may be made without departing from the technical solutions described in the claims.

Claims

1. A method for molten salt regeneration of retired lithium battery cathode materials, characterized in that, Includes the following steps: S1: Disperse retired ternary cathode material in lithium oxalate solution, add the resulting mixture dropwise to ethanol solution, and sinter the resulting solid at low temperature in an oxygen-containing atmosphere to obtain pre-regenerated material; S2: The pre-regenerated material is mixed evenly with the metal oxide additive and calcined at high temperature in an oxygen-containing atmosphere to obtain a regenerated cathode material coated with a coating layer. The metal oxide additive is selected from at least one of niobium pentoxide, molybdenum trioxide, tantalum pentoxide, and tungsten pentoxide.

2. The method according to claim 1, characterized in that, In S1, the retired ternary cathode material is cathode powder recovered from lithium-ion batteries that have reached the end of their cycle life. Its chemical composition is LiNixCoyMnzO2 or LiNixCoyMnzO2, where x+y+z=1, and 0.34≤x≤0.9, 0.05≤y≤0.3, and 0.05≤z≤0.

4. In the retired ternary cathode material, the lithium loss is 5%~30%, the surface residual alkali content is 0.5~10.0 wt%, and the cation mixing degree is 3%~10%.

3. The method according to claim 1, characterized in that, In S1, the mass ratio of the decommissioned ternary cathode material to the lithium oxalate solution is 1:10 to 1:

50. And / or, the concentration of the lithium oxalate solution is 0.2-1.0 mol / L.

4. The method according to claim 1, characterized in that, In S1, the low-temperature sintering time is 2-6 hours, and the sintering temperature is 300-500℃; And / or, the heating rate is 2-10°C / minute.

5. The method according to claim 1, characterized in that, In step S2, the amount of metal oxide additive added is 0.5%-5% of the mass of the pre-regenerated material.

6. The method according to claim 5, characterized in that, The amount of metal oxide additive added is 0.5%-2% of the mass of the pre-recycled material.

7. The method according to claim 1, characterized in that, In S2, the high-temperature calcination time is 6-12 hours, and the sintering temperature is 800-1000℃. And / or, the heating rate is 2-10°C / minute.

8. The method according to claim 1, characterized in that, The average grain size of the obtained recycled cathode material is 200-800 nm; the coating layer is a lithium-ion conductive layer containing at least one of niobium, molybdenum, tantalum or tungsten; the coating layer thickness is 5-30 nm.

9. A regenerated cathode material prepared by the method according to any one of claims 1-8.

10. The application of the recycled cathode material as described in claim 9 in the field of solid-state lithium-ion batteries and its preparation.

Citation Information

Patent Citations

  • Fused salt repairing and recycling method for waste ternary positive electrode material

    CN116924486A

  • Lithium ion battery positive electrode material regeneration method based on synergistic effect of doping and fused salt reconstruction

    CN121149475A